Cross-Sectionnal Patterns in Moroccan Sock Returns: A Fama-French Perspective - Benfeddoul, Safae; Alaoui Taib, Asmâa (International Journal of Economics and Financial Issues, 2024)
Drawing on the Fama and French models, we examine the role of market factor (beta), fundamental characteristics (size, book-to-market, profitability and investment) and the momentum in explaining cross-sectional stock returns in the Moroccan market. The sample consists of non-financial stocks over the period from July 2008 to June 2020. In this research and for the first time, we contribute to the current body of asset pricing literature by embracing three different empirical methodologies. First, we use an adaptation of cross-sectional methodologies from Fama and MacBeth (1973) and Fama and French (1992). Second, we opt for portfolios as dependent variables to reduce potential estimation errors associated with individual stocks. Third, we specifically adjust for the errors-in-variables issue using the methodology proposed by Brennan et al. (1998). Our results indicate that beta coefficients are statistically insignificant in both first and second methodologies. Furthermore, none of the characteristic’s variables meet the criteria for a good explanatory variable, as they fail to consistently exhibit a significant level of significance in all cases. Generally, the momentum factor emerges as the most promising variable. We conclude that the tested models are incomplete in explaining variations in Moroccan stock returns. Even after adjusting for model risk, some effects persist.